De un estado excluyente a un estado intercultural - Román Márquez, Alvaro (2024)
Although they have passed about seven years of existence and validity of the Conslitution of the Republic of Ecuador we can not yet dare to say that the faw is equal validity with lts sociologlcal validity. On leading lnstitutions havíng theír statements in accordance with the constítutional movement neo that left its mark on almost all constítutions ín Latin America there is a high dose of disbelief In a bread sector of political and academic opinion still reluctant to flnd the desired lransformation the foundalions on which our rule of law is based.One of !hose pillars that collects new constitutional neo charge of the constitution has to do with the issue of multiculturalism and legal pluralism, principies upon which the ordinary and indigenous justice as two complementary sources ol independent law is buill and hlerarchically homogeneous. Multiculturallsm as the supreme ideal has its pitlalls in the constitutional. and legal rules themselves resistan! to accept a theoretical construct - law that requires genuina particlpation of all peoples and nationalilíes that make up our society in the establishment, structure ol all state institutions and the obligatory presence they should have In the desígn and implementation of public policies that go beyond the mere discursiva level.